Educational policy innovations : levelling up and sustaining educational achievement - Lee, Wing On; Low, Ee Ling (Education Innovation Series, 2014)
This volume presents how high performing education systems over the world are constantly innovating their educational policies to nurture their citizens for the challenges of the future economy and the anticipation of the unknown. This volume includes a state-of-the-art review of the literature in this field, several commissioned focal chapters focusing on the distinctive case of Singapore and internationally commissioned chapters of several other accomplished education systems around the world. A comparative study of Singapore against other high performing education systems is included to provide greater insights to the possible applications to other education systems.